Trade and wage disparities in South Africa - Brian Tavonga Mazorodze (Cogent Economics & Finance, 2021)
Literature on trade and wage disparities has gained prominence since the mid-90s following the push for trade liberalization across the globe. Despite the 26 years of empirical research, however, questions of whether trade closes or widens the wage gap remain relevant today, particularly in countries such as South Africa where income inequality remains a persistent policy concern. Against this background, this paper contributes to the literature by examining the effect of trade on relative wages between skilled and low-skilled workers in South Africa using a local municipality-level dataset observed between 1995 and 2019. Results from the system GMM estimator confirm that trade has had a positive and non-trivial effect on wage disparities in the past two decades. When decomposed into exports and imports, it is the latter that appears to have added a relatively large wage premium on skilled workers at the expense of low-skilled workers. This result is crucial in designing both trade and industrial policies. In particular, it brings to the fore the need for targeted interventions that protect low-skilled workers. Such interventions may include programs for skills upgrade and trade protectionist policies in low-skill labour-intensive industries.
Keywords: 330; low-skilled workers; semi-skilled; skilled-workers; South Africa; trade wage disparities